Life Cycle Analysis of the Panela Agroindustry and Intensification for its Development: A Bibliographical Review - Walter Francisco Quezada Moreno; Walter D. Quezada Torres; Sandra Lissette Recalde Luna; Erenio González Suárez; Franklin Antonio Molina Borja; Nancy Fabiola Moreano Terán; Amaury Pérez Martinez (Research Highlights in Agricultural Sciences Vol. 6, 2022)
The study permitted the identification of sensitive environmental factors generated in all operations carried out in a panela agroindustry for the purposes of diversification, productivity, quality, and safety. According to the Life Cycle Analysis (LCA) methodology, the outcomes of the Environmental Impact Assessment (EIA) demonstrate that in all impact categories, the industrial stage of honey, panela, and sugar production cause greater environmental impact, with the latter two being the most representative. Panela is non-centrifugal cane sugar (NCS), a high carbohydrate-content food obtained by evaporation of water in sugarcane juice. However, according to Ecuadorian environmental legislation, the panela agroindustry’s impacts are moderate and classified as type II, so intensive corrective measures are not required. However, it necessitates preventive measures aimed at mitigating impacts, given that it is a subsector of the sugar cane industry with production units located throughout the country in areas with favorable conditions for sugar cane cultivation.